TRADISI TAHLILAN SEBAGAI MODEL ETNOPEDAGOGI KOMUNAL DALAM PENDIDIKAN KARAKTER MASYARAKAT MUSLIM BANTEN - Suyani Armin; Asep Muhyidin; Aan Asphianto; Ujang Jamaludin (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to analyze the tahlilan tradition as a communal ethnopedagogy model in character education within the Banten Muslim community. The focus is directed toward how character values are culturally internalized outside the formal education environment. Method: This study employs a qualitative approach with a field research design, utilizing participant observation, in-depth interviews with religious and community leaders in Banten, and content analysis of the tahlilan ritual structure. Result: The findings indicate that the tahlilan tradition in the Banten Muslim community is not merely a religious ritual but functions as an effective communal pedagogical space. It facilitates the transmission of noble character values such as religiosity, mutual cooperation (gotong royong), tolerance, and social equality, which are adopted by the younger generation through sustained active involvement. The integration of these local values strengthens affective competence and social awareness amidst global changes. Novelty: The novelty of this study lies in the deconstruction of the tahlilan tradition—typically examined through theological or sociological lenses—now integrated as a conceptual communal ethnopedagogy model within the informal social system of character education.